PRONUNCIATION CORRECTION METHODS FOR LEARNERS OF ENGLISH AS A FOREIGN LANGUAGE: A SYSTEMATIC REVIEW (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
Abstract. This article presents a systematic review of pronunciation correction methods for learners of English as a Foreign Language (EFL). The aim of the study is to compare traditional and technology-based approaches to pronunciation correction and to evaluate their effectiveness for Kazakh and Russian-speaking learners. The research material consists of eight articles published between 2016 and 2024 and selected according to predefined inclusion and exclusion criteria. The study employs a systematic review methodology based on the qualitative synthesis of findings from the selected studies.The results indicate that traditional pronunciation instruction, including explicit phonetic teaching, IPA-based exercises, and corrective feedback strategies, is effective in reducing first-language interference and improving segmental pronunciation accuracy. Technology-based approaches relying on Artificial Intelligence (AI) and Automatic Speech Recognition (ASR) enhance learner autonomy and provide extensive practice opportunities; however, they exhibit certain limitations in independently addressing complex phonological errors. Accordingly, the study supports the effectiveness of a hybrid instructional model that integrates traditional pronunciation teaching with technology-assisted practice. The findings have both theoretical and practical significance, offering insights for improving pronunciation instruction in EFL classrooms and guiding future empirical research.